2015
DOI: 10.18404/ijemst.17155
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ Views on Ghana’s Undergraduate Mathematics Education

Abstract: This paper synthesizes the views of 6 university lecturers on Ghana's undergraduate mathematics education. These views were expressed during a mathematics workshop sensitization program on the "contribution of undergraduate mathematics education to the Ghanaian economy." The data consisting of open-ended questions followed by semi-structured interviews were analyzed using qualitative analysis. The results of this study indicated that lecturers' teaching methods do not enable students to connect theories with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Other studies focus on the ways in which practices within a university might explicitly affect student motivations and attitudes towards critical thinking. The lecturers in Assuah and Ayebo's (2015) and Omingo's (2016) studies in Ghana and Kenya, respectively, indicated that students were more motivated when they could see connections between their learning and their future careers. Connections to activities with meaningful outcomes also seemed to improve student attitudes.…”
Section: Student Attitudes and Motivationsmentioning
confidence: 99%
“…Other studies focus on the ways in which practices within a university might explicitly affect student motivations and attitudes towards critical thinking. The lecturers in Assuah and Ayebo's (2015) and Omingo's (2016) studies in Ghana and Kenya, respectively, indicated that students were more motivated when they could see connections between their learning and their future careers. Connections to activities with meaningful outcomes also seemed to improve student attitudes.…”
Section: Student Attitudes and Motivationsmentioning
confidence: 99%